2015
DOI: 10.1111/jphp.12469
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insight into the dramatic improvement of probucol dissolution in neutral solutions by solid dispersion in Eudragit E PO with saccharin

Abstract: Preparation of ternary solid dispersion is a potential method of improving drug solubility and absorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…The surface activity of EUD-E was also affected by pH and ionic strength. 56) It was hypothesized that the surfactant function of E-SD, which resulted in the formation of a micelle-like structure, was related to reprecipitation inhibition. Fluorescence measurement using pyrene as a probe confirmed that E-SD formed micelle-like structures.…”
Section: Interaction Between Drug and Modified Eud-e In Aqueous Solutionmentioning
confidence: 99%
“…The surface activity of EUD-E was also affected by pH and ionic strength. 56) It was hypothesized that the surfactant function of E-SD, which resulted in the formation of a micelle-like structure, was related to reprecipitation inhibition. Fluorescence measurement using pyrene as a probe confirmed that E-SD formed micelle-like structures.…”
Section: Interaction Between Drug and Modified Eud-e In Aqueous Solutionmentioning
confidence: 99%
“…As suitable pharmaceutical polymers for the development of ASDs are limited, research has focused on the development of modified polyelectrolyte matrices combining the already used polymers with small molecular additives [ 125 , 126 ]. From this point of view, ternary solid dispersions of probucol, Eudragit EPO, and saccharin were formed by cryogenic grinding.…”
Section: Modified Polyelectrolyte Matricesmentioning
confidence: 99%
“…Electrostatic interactions between the amide group of saccharin and the tertiary amino group of the polymer were reported, while the preservation of the amorphous state was attributed to the hydrophobic interactions between the drug and Eudragit EPO. In addition, the dissolution profile of probucol in neutral solutions was remarkably enhanced due to these intermolecular interactions, in comparison to the binary mixtures without saccharin [ 125 ].…”
Section: Modified Polyelectrolyte Matricesmentioning
confidence: 99%
“…It has been used as a taste-masking agent (Taki et al, 2017) and provides a glossy and slippery easy-to-swallow finishing. Its use is well established for pharmaceutical purposes as a solubility enhancer (Higashi et al, 2016;Saal et al, 2017Saal et al, , 2018, stability enhancer (Ochi et al, 2016) and in the manufacturing of immediate release dosage forms (Qiao et al, 2010;Sadia et al, 2016;Yang et al, 2015). Its compatibility with hot melt extrusion has also been previously demonstrated (Ashour et al, 2016;Li et al, 2016a;Li et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%